2003
DOI: 10.1007/3-540-45105-6_3
|View full text |Cite
|
Sign up to set email alerts
|

AntClust: Ant Clustering and Web Usage Mining

Abstract: Abstract. In this paper, we propose a new ant-based clustering algorithm called AntClust. It is inspired from the chemical recognition system of ants. In this system, the continuous interactions between the nestmates generate a "Gestalt" colonial odor. Similarly, our clustering algorithm associates an object of the data set to the odor of an ant and then simulates meetings between ants. At the end, artificial ants that share a similar odor are grouped in the same nest, which provides the expected partition. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…Several techniques have been developed to solve clustering problems and those based on the Swarm Intelligence (SI) paradigm seem to be specially attractive because of their robust performance [4,30,31,50]. 2 In those cases where clustering techniques are applied to corpora containing very short documents, further difficulties are introduced due to the low frequencies of the document terms.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been developed to solve clustering problems and those based on the Swarm Intelligence (SI) paradigm seem to be specially attractive because of their robust performance [4,30,31,50]. 2 In those cases where clustering techniques are applied to corpora containing very short documents, further difficulties are introduced due to the low frequencies of the document terms.…”
Section: Introductionmentioning
confidence: 99%
“…ACSC employs the sliding window model when dealing with data streams so at each iteration a fixed size chunk of data is considered. The process for finding ε at each window is based on the algorithm presented in [11]. ε is calculated as the mean value of n Euclidean distance measures, dist(i, j) ∈ [0, 1], between n randomly chosen i and j data points in the current window.…”
Section: Finding the ε-Neighbourhoodmentioning
confidence: 99%
“…The algorithm computes the clusters using K-means, which, again, is limiting in both the number and shape of the clusters that it can potentially find. A variation on the Leader Ant algorithm was proposed in [11] as an accurate and inexpensive agglomerative clustering algorithm. Other ant clustering algorithms are based on the 'pick-and-drop' model proposed in [5].…”
Section: Introductionmentioning
confidence: 99%
“…This method is easily applicable to many fields including web mining and other unsupervised domains. There are many cases of ANTCLUST implementations [Labroche et al, 2003a], [Labroche et al, 2003b], including variants that have been shown to separate noise from data [Zaharie and Zamfirache], credit evaluation of small enterprises [Xue-chun et al, 2007], and web-mining [Inbarani and Thangavel, 2006].…”
Section: Type III -Clustering Inspired By the Chemical Recognition Symentioning
confidence: 99%